Bringing French public debt down: The options for fiscal consolidation - Balazs Egert (Center for Economic Studies and ifo Institute (CESifo), 2012)
France has a track record of persistent general government deficits, partly reflecting pro-cyclical fiscal policies in upswings. This has resulted in a quadrupling of its public debt-to-GDP ratio since the 1970s to above 80% of GDP. Reducing public debt is crucial because a high level of public debt may hamper long-term growth and may have a direct impact on fiscal sustainability if long-term interest rates rise. Bringing back public debt to 60% of GDP even by 2030 would require a fiscal effort of 4 to 5 percentage points of GDP (under the assumption of unchanged long-term rates), implying permanent primary general government surpluses, which is very ambitious in view of French fiscal history since 1970. The government's consolidation programme, which is aimed at reducing the general government deficit to 3% of GDP by 2013, represents around two-thirds of this effort. This study analyses how fiscal governance could be improved by the creation of a structural deficit rule and looks at ways the public deficit could be lowered. With France already having a very large public sector, most of the effort should be borne by holding down spending. Better control of the public wage bill, increasing public-sector efficiency and tackling age-related costs are the obvious candidates to contain expenditure. On the revenue side, there is significant potential for cutting tax expenditures. Furthermore, eliminating distortions in the tax base would encourage economic growth.
Keywords: H19; H21; H23; H24; H25; H51; H54; H55; H62; H63; H71; H72; 330; public debt; general government deficit; fiscal rule; structural deficit; fiscal council; government spending; tax revenues; local governments; pension system; healthcare; tax expenditure; Haushaltskonsolidierung; Öffentliche Schulden; Frankreich